An ICT agripreneurship guide: A path to success for young ACP entrepreneurs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2017)
This Handbook provides a step-by-step roadmap designed to equip aspiring ICT entrepreneurs, with the information and knowledge they need to start an ICT-based business in the agricultural sector, outlining key opportunities and challenges that will be encountered along the way. Using real-life examples, it provides strategies and pathways for averting common mistakes faced by early-stage entrepreneurs. Topics covered include agricultural value chains and their stakeholders, ICT business challenges, effective business plans and models for designing, funding and scaling ventures.